Green synthesis of gold nanoparticles and its application for the trace level determination of painter's colic1. Issue 21 (6th March 2015) - Karuppiah, Chelladurai; Palanisamy, Selvakumar; Chen, Shen-Ming; Emmanuel, R.; Muthupandi, K.; Prakash, P.
<x xml:space="preserve">Abstract</x> The green synthesis of metal nanoparticles is found to be more attractive in various disciplines, including in analytical chemistry for heavy metal ion sensing.